2009
DOI: 10.5713/ajas.2009.80571
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Oak Acorn (Quercus ilex) Based Diet on Growth Performance and Meat Fatty Acid Composition of Broilers

Abstract: This experiment was conducted to compare the effects of oak acorns and corn on broilers growth performance, carcass characteristics and meat fatty acid (FA) composition according to different ages of broilers. Two separate groups of 400 male broilers, reared for six weeks, were fed diets containing 33.5% green oak acorns (GO) and 67% of corn (C), respectively. At day 35, the body weight of the chickens fed the GO diet was 12% lower (p<0.05) compared with controls (C). However, at day 56 birds reached similar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In this regard, Wood and Enser (1997) mentioned a minimum recommendation of 0.45 for the PUFA/SFA ratio. In the current study, acceptable levels of total PUFA/SFA have been observed (0.42 to 0.66, Table 5 ), similar to those reported in other poultry species fed on acorns (0.7 in broilers; Bouderoua et al, 2009 ) and higher than that reported in other livestock species (0.15 in lambs, Keddam et al, 2010 ; or 0.39 in goats, Turner et al, 2015 ). Thus, the PUFA levels and the PUFA/SFA ratio of geese raised in the organic dehesa system were similar to the recommended ratio.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In this regard, Wood and Enser (1997) mentioned a minimum recommendation of 0.45 for the PUFA/SFA ratio. In the current study, acceptable levels of total PUFA/SFA have been observed (0.42 to 0.66, Table 5 ), similar to those reported in other poultry species fed on acorns (0.7 in broilers; Bouderoua et al, 2009 ) and higher than that reported in other livestock species (0.15 in lambs, Keddam et al, 2010 ; or 0.39 in goats, Turner et al, 2015 ). Thus, the PUFA levels and the PUFA/SFA ratio of geese raised in the organic dehesa system were similar to the recommended ratio.…”
Section: Resultssupporting
confidence: 88%
“…The general consensus is that this corresponds to a ω6/ω3 ratio of ~6:1 ( Wijendran and Hayes, 2004 ). In the goose meat produced, higher values for the ω6/ω3 ratio (20:1) were observed compared to other poultry species (between 8:1 and 18:1, Has-Schön et al, 2008 ; Bouderoua et al, 2009 ; Liu and Zhou, 2013 ). Therefore, it is recommendable to introduce alternative supplements into the diet, such as linseed or high oleic sunflower seeds, which help to reduce the ω6/ω3 ratio ( Azcona et al, 2008 ).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Many scientific reports have illustrated on the use of phenolic‐rich plant and fruit extracts as inhibitors of lipid oxidation and promoters of shelf life and quality in chicken meat products (Hwang and others ; Estevez ). Acorns are known for their indisputable benefits as feeds for pigs and broilers in terms of oxidative stability and quality of the derived meat products (Ventanas and others ; Bouderoua and others ). In our experiment, the direct addition of acorn extract was highly effective in the control of lipid and protein oxidative degradation in RTE chicken patties.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, geese are usually produced on specialized commercial farms, and although the meat from intensively raised stocks has a soft texture, it is considered by many traditional consumers to have less flavour (FAO, 2004). Thus, alternative rearing systems such as dehesa emerge as ecosystems of high ecological value for the extensive production of high-quality meat with outstanding and unique characteristics (Rey et al, 2006;Bouderoua et al, 2009;Keddam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%